Protecting great apes from disease: Compliance with measures to reduce anthroponotic disease transmission. Issue 5 (4th September 2022) - Nuno, Ana; Chesney, Chloe; Wellbelove, Maia; Bersacola, Elena; Kalema‐Zikusoka, Gladys; Leendertz, Fabian; Webber, Amanda D.; Hockings, Kimberley J.
Abstract: The emergence of infectious diseases, such as COVID‐19, impacts livelihood strategies and conservation tools reliant on human‐wildlife interactions, such as wildlife‐based tourism and research. This is particularly relevant to great ape conservation, as humans and great apes are susceptible to being infected by similar pathogens. Evidence‐based strategies are required to prevent infectious disease transmission to great apes and people involved in, or living close to, tourism sites. The development of disease‐safe recommendations and their effective operationalisation require an understanding of what affects visitor compliance. Based on an international sample of past ( N  = 420) and potential future visitors ( N  = 569) to wild great ape tourism sites in Africa, we used an online questionnaire to characterise visitors' practices, assess expectations (e.g. about proximity to great apes) and identify key factors related to potential compliance with disease mitigation measures. This was implemented adapting a framework from health literature (the Health Belief Model; HBM), particularly focused on reducing COVID‐19 transmission at an early stage of the pandemic. Visitors expressed less willingness to being vaccinated against COVID‐19 (which, at the time our survey was conducted, had only just started being administered to very high‐risk groups), wearing a facemask during trekking (although willing when viewing the apes) and quarantine after international travel before visiting great apes. Region of nationality, expectations about the visitor experience and perceived effectiveness of specific measures were important factors explaining variation in potential compliance across multiple behaviours. By gaining a better understanding of what fosters compliance with disease mitigation measures, we obtained insights that are essential for assessing feasibility, facilitating effective communication, and guiding implementation at great ape tourism sites with importance not only for COVID‐19 but also for other infectious diseases more broadly, particularly at early stages of future pandemics. While requiring adaptive management as situations evolve (e.g. vaccination becoming more widely accessible), these will contribute towards a more sustainable visitor experience that can effectively deliver positive outcomes for people and biodiversity. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog. Resum: L'emergència de malalties infeccioses, com la COVID‐19, impacta les estratègies de subsistència i les eines de conservació que depenen de les interaccions entre els humans i la fauna salvatge, com ara el turisme i la investigació basats en la vida silvestre. Això és particularment rellevant per a la conservació dels grans simis, ja que els humans i els grans simis són susceptibles de ser infectats per patògens similars. Calen estratègies basades en l'evidència per prevenir la transmissió de malalties infeccioses als grans simis i a les persones que participen en el turisme o viuen a prop de llocs turístics. Elaborar recomanacions per evitar malalties i posar‐les en pràctica de manera efectiva requereix entendre què afecta el compliment d'aquestes per part dels visitants. Ens vam basar en una mostra internacional de visitants passats ( N  = 420) i possibles futurs visitants ( N  = 569) a llocs turístics de grans simis salvatges a l'Àfrica i vam utilitzar un qüestionari en línia per caracteritzar les pràctiques dels visitants, avaluar‐ne les expectatives (per exemple, sobre la proximitat amb els grans simis) i identificar‐ne els factors clau relacionats amb el possible compliment de les mesures de mitigació de malalties. Això es va dur a terme adaptant un marc de treball de la literatura sanitària (el Model de Creences de Salut; HBM, per les seves sigles en anglès), especialment centrat en reduir de la transmissió de la COVID‐19 en una fase primerenca de la pandèmia. Els visitants es van mostrar menys disposats a vacunar‐se contra la COVID‐19 (que, en el moment en què es va realitzar la nostra enquesta, tot just s'havia començat a administrar a grups de moult alt risc), a dur una mascareta durant la visita (tot i que estaven disposats a posar‐se‐la quan veiessin els simis) i a sotmetre's a una quarantena després d'un viatge internacional abans de visitar els grans simis. La regió on s'agrupa la nacionalitat dels visitants, les expectatives dels visitants sobre l'experiència i l'eficàcia percebuda de les mesures específiques van ser factors importants que expliquen la variació en el possible compliment de diversos comportaments. Arran d'entendre millor què fomenta el compliment de les mesures de mitigació de malalties, vam obtenir informació essencial per avaluar‐ne la viabilitat, facilitar‐ne una comunicació eficaç i orientar‐ne la implementació als llocs turístics de grans simis. Això és important, no només per a la COVID‐19, sinó també per altres malalties infeccioses en general, especialment en les primeres etapes de futures pandèmies. Malgrat calgui adaptar la gestió a mesura que les situacions evolucionen (per exemple, quan la vacunació esdevé àmpliament accessible), el coneixement obtingut contribuirà a una experiència més sostenible pels visitants, que pot oferir resultats positius per a la gent i la biodiversitat. Résumé: L'apparition de maladie infectieuse comme le COVID‐19, a des impacts sur les moyens de subsistance ainsi que des approches de conservation telles que la recherche et le tourisme axé sur la faune. Ceci est particulièrement pertinent pour la conservation des grands singes, car les humains et les grands singes sont susceptibles d'être infectés par les mêmes agents pathogènes. L'identification en empirie de stratégies sont nécessaires pour éviter la transmission de maladies infectieuses aux grands singes et aux personnes impliquées dans les activités touristiques ou vivant à leur proximité. Le développement de recommandation pour éviter les maladies nécessitent une compréhension de ce qui détermine la conformité du comportement des visiteurs. En nous appuyant sur un échantillonage de touristes internationaux actuelles ( N  = 420), et potentielles ( N  = 569), de ces sites de tourisme des grands singes sauvages en Afrique, nous avons utilisé un questionnaire, pour caractériser les pratiques des visiteurs, évaluer leurs attentes (par exemple, envers la possibilité d'approcher les singes) et identifier les facteurs clés liés au respect potentiel des mesures d'atténuation des maladies. Ces recherches ont été mis en œuvre en adaptant un cadre de bonne pratique pour la santé humaine (Health Belief Model; HBM), avec l'objectif de réduire la transmission du COVID‐19 à un stade précoce de la pandémie. Les visiteurs exprimaient peux de volonté de se vacciner contre le COVID‐19 (qui, au moment où notre enquête a été menée, venait d'être administré qu'aux groupes les plus à risque), de porter un masque facial pendant le trekking (contrairement avec la volonté d'en porter pendant les rencontres avec les singes), et de se mettre en quarantaine après tout voyage international avant de visiter les singes. La région d'origine des visiteurs, les attentes concernant l'expérience du visiteur et la perception de l'efficacité des mesures spécifiques étaient des facteurs importants pour expliquer les différences en conformité potentielle entre plusieurs comportements. En ayant une meilleure compréhension de ce qui favorise l'appréciation des mesures pour limiter la transmission de maladie, nous avons obtenu des informations essentielles pour faciliter une communication efficace, et pour guider la mise en place de ces mesures pour le tourisme des grands singes, non seulement pour le COVID‐19 mais aussi pour d'autres maladies infectieuses, en particulier dans le début de futures pandémies. Nécessitant une gestion adaptative à mesure que les situations évoluent (par exemple, la vaccination devient plus largement accessible), ces mesures contribueront à une expérience des touristes plus durable et donc qui peuvent plus effectivement produire des résultats favorables pour les humains et la biodiversité. Abstrakt: Das Auftreten von Infektionskrankheiten wie COVID‐19 hat Auswirkungen auf Lebensunterhaltstrategien und auf Naturschutzmaßnahmen, die von der Interaktion zwischen Mensch und Wildtieren abhängen, wie z. B. Wildtiertourismus und Forschung. Dies ist besonders wichtig für den Schutz von Menschenaffen, da Menschen und Menschenaffen von ähnlichen Krankheitserregern befallen werden können. Es werden evidenzbasierte Strategien benötigt, um die Übertragung von Infektionskrankheiten auf Menschenaffen und Menschen, die an touristischen Attraktionen beteiligt sind oder in deren Nähe leben, zu verhindern. Die Entwicklung von Empfehlungen zur Vermeidung von Krankheiten und ihre wirksame Umsetzung erfordern ein Verständnis der Faktoren, die die Einhaltung der Vorschriften seitens der Besucher beeinflussen. Auf der Grundlage einer internationalen Stichprobe ehemaliger ( N  = 420) und potenzieller künftiger Besucher ( N  = 569) von Tourismusgebieten für wildlebende Menschenaffen in Afrika haben wir einen Online‐Umfrage durchgeführt, um die Gewohnheiten der Besucher zu erfassen, ihre Erwartungen (z. B. in Bezug auf die Nähe zu Menschenaffen) zu bewerten und Schlüsselfaktoren im Zusammenhang mit der potenziellen Einhaltung von Maßnahmen zur Eindämmung von Krankheiten zu ermitteln. Dabei wurde ein Framework aus der Gesundheitsliteratur (Health Belief Model; HBM) adaptiert, das sich insbesondere auf die Reduzierung der COVID‐19‐Übertragung in einem frühen Stadium der Pandemie konzentriert. Die Besucher waren weniger bereit, sich gegen COVID‐19 impfen zu lassen (diese Impfung war zum Zeitpunkt unserer Umfrage gerade erst für Hochrisikogruppen freigegeben worden), während des Trekkings einen Mundschutz zu tragen (obwohl sie dazu bereit waren, wenn sie die Affen sahen) und nach internationalen Reisen in Quarantäne zu gehen, bevor sie Menschenaffen besuchten. Die Nationalität, die Erwartungen an das Besuchererlebnis und die wahrgenommene Wirksamkeit spezifischer Maßnahmen waren wichtige Faktoren, die die Unterschiede in der potenziellen Einhaltung der verschiedenen Verhaltensweisen erklären. Durch ein besseren Verständnisses darüber, was die Einhaltung von Maßnahmen zur Krankheitsbekämpfung fördert, haben wir Erkenntnisse gewonnen, die für die Bewertung der Durchführbarkeit, die Verbesserung einer wirksamen Kommunikation und die Steuerung der Umsetzung in touristischen Standorten für Menschenaffen von Bedeutung sind, und zwar nicht nur für COVID‐19, sondern auch für andere Infektionskrankheiten im Allgemeinen, insbesondere in frühen Stadien künftiger Pandemien. Diese Maßnahmen erfordern zwar ein anpassungsfähiges Management, je nachdem, wie sich die Situation entwickelt (z. B. wenn die Impfung besser zugänglich wird), werden aber zu einem nachhaltigeren Besuchererlebnis beitragen, das sich positiv auf die Menschen und die biologische Vielfalt auswirkt. सार: कोविड ‐19 जैसे संक्रामक रोगों के उद्भव का दुष्प्रभाव मानवों‐वन्यजीवों के पारस्परिक सम्बन्धों से जुड़ी आजीविका के साधनों एवं संरक्षण के उपायों पर देखा गया है, जैसे कि, वन्यजीव‐आधारित पर्यटन और अनुसंधान । यह विशेष रूप से वनमानुषों के संरक्षण के लिए प्रासंगिक है, क्योंकि मनुष्य और वनमानुष के रोगाणुओं में समानता होने की प्रबल संभावना हैं । वनमानुषों और इंसानो के बीच पारस्परिक रोगों के आदान‐प्रदान की रोकथाम के लिए और पर्यटन स्थलों में शामिल या उनके करीब रहने वाले लोगों के बीच होने वाले संक्रमणों के तहत साक्ष्य जुटाने की आवश्यकता है । रोग‐संक्रमण सुरक्षा से जुड़ी अनुशंसा के विकास और उन मापदंडो के प्रभावी संचालन के लिए यह समझने की आवश्यकता है कि पर्यटकों में रोग‐शमन का अनुपालन किन बिंदुओं से प्रभावित होता है । रोग‐शमन के संभावित अनुपालन से संबंधित प्रमुख कारकों की पहचान करने के लिए हमने अफ्रीका में जंगली वनमानुषों वाले पर्यटन स्थलों के पूर्व (संख्या = 420) और निकट भविष्य में संभावित आगंतुकों (संख्या = 569) के एक अंतरराष्ट्रीय नमूने का आकलन किया । एक ऑनलाइन प्रश्नावली का उपयोग कर हमने आगंतुकों की उन प्रथाओं एवं अपेक्षाओं को चिह्नित किया जो रोगाणुओं के आदान‐प्रदान को प्रभावित करते हैं । उदाहरण के लिए, पर्यटकों द्वारा वनमानुषों को निकट से अनुभव करने की इच्छा । इसे समझने के लिए हमने स्वास्थ्य से जुड़े साहित्य (हेल्थ बिलीफ मॉडल; एचबीएम) के अंतर्गत स्वीकृत रूपरेखा को आधार बनाया । विशेषतः, इस प्रक्रिया के लिए हमने कोविड ‐19 महामारी के प्रारंभिक चरण में संचरण को कम करने वाले बिंदुओं पर ध्यान केंद्रित किया । पर्यटकों ने अंतर्राष्ट्रीय उड़ान के बाद क्वारेंटीन, ट्रेकिंग के दौरान फेसमास्क पहनने (हालाँकि वो वनमानुषों को देखते समय मास्क पहनने को तैयार थे) और कोविड ‐19 टीकाकरण को लेकर उत्साह दिखाया (जबकि हमारे सर्वेक्षण के समय प्रारंभिक स्तर पर टीकाकरण केवल बहुत उच्च जोखिम वाले समूहों के लिए ही उपलब्ध था) । पर्यटकों के व्यवहारों में संभावित अनुपालन में भिन्नता को स्पष्ट करने वाले महत्वपूर्ण कारक थे: उनकी राष्ट्रीयता, उनकी अपेक्षाएँ और उनके द्वारा विशिष्ट उपायों की प्रभावशीलता का महसूस किया जाना । इस शोध कार्य के तहत हमने रोग‐शमन के अनुपालन को बढ़ावा देने की बेहतर समझ के उपयोग से ऐसी अंतर्दृष्टि विकसित की जो व्यवहार्यता का आकलन करने, प्रभावी संचार की सुविधा प्रदान करने और वनमानुषों से जुड़े पर्यटन स्थलों पर कार्यान्वयन का मार्गदर्शन करने के लिए न केवल कोविड ‐19, बल्कि अन्य संक्रामक रोगों के लिए भी महत्वपूर्ण है; विशेषतः भविष्य में होने वाली महामारियों के प्रारंभिक चरणों के लिए । हमारे परिणाम बताते हैं की विषम परिस्थितियों में अनुकूल प्रबंध पर्यटकों के लिए एक अधिक स्थायी और सुखद अनुभव की दिशा में योगदान देंगे जो लोगों और जैव‐विविधता के लिए सकारात्मक सिद्ध होगा । टीकाकरण अभियानों का विकसित होता व्यापक रूप और इसकी सुलभता इस बात का उदाहरण है । Abstrak: Kemunculan penyakit menular, seperti COVID‐19, berdampak pada strategi penghidupan dan upaya konservasi yang bergantung pada interaksi manusia‐satwa liar, seperti wisata dan penelitian berbasis satwa. Fenomena ini terutama relevan bagi konservasi kera besar, karena manusia dan kera besar rentan terinfeksi oleh patogen yang serupa. Strategi berbasis bukti dibutuhkan untuk mencegah transmisi penyakit menular terhadap kera besar dan masyarakat yang terlibat, atau tinggal di dekat, area wisata. Pengembangan rekomendasi untuk mencapai kondisi bebas penyakit dan pelaksanaannya yang efektif membutuhkan pemahaman akan apa yang memengaruhi kepatuhan pengunjung. Menggunakan sampel pengunjung internasional terdahulu ( N  = 420) dan pengunjung potensial ( N  = 569) yang akan datang ke lokasi wisata kera besar liar di Afrika, kami melakukan survei kuesioner online untuk mengkarakterisasi perilaku pengunjung, mengkaji harapan mereka (contoh: tentang jarak ke kera besar) dan mengindentifikasi faktor kunci terkait potensi kepatuhan terhadap tindakan mitigasi penyakit. Implementasi ini dilakukan dengan mengadaptasi pendekatan dari literatur kesehatan (the Health Belief Model/Model Kepercayaan Kesehatan, HBM), dengan fokus pada pengurangan transmisi COVID‐19 di tahap awal pandemi. Pengunjung melaporkan keengganan untuk divaksinasi COVID‐19 (dimana, ketika survei kami dilakukan, vaksinasi baru diberikan kepada kelompok sangat rentan), menggunakan masker wajah selama perjalanan (walaupun mereka bersedia memakainya ketika melihat kera) dan karantina setelah perjalanan internasional sebelum mengunjungi kera besar. Wilayah kewarganegaraan, harapan atas pengalaman kunjungan dan persepsi akan efektivitas tindakan yang diberlakukan menjadi faktor penting yang menjelaskan variasi potensi kepatuhan seseorang di berbagai tipe perilaku. Melalui pemahaman akan faktor yang mendorong kepatuhan terkait mitigasi penyakit, kami memperoleh informasi penting untuk mengkaji kelayakan, memfasilitasi komunikasi efektif, dan mengarahkan pelaksanaan aturan di lokasi wisata kera besar yang penting tidak hanya bagi COVID‐19 tapi juga penyakit menular lainnya, terutama di awal masa pandemi ke depannya. Walaupun pengelolaan adaptif dibutuhkan seiring dengan perkembangan situasi (contoh: ketika vaksinasi dapat diakses secara luas), tahapan di atas akan berkontribusi terhadap keberlanjutan pengalaman pengunjung yang secara efektif menghasilkan luaran positif bagi manusia dan biodiversitas. Sommario: L'emergenza delle malattie infettive, come il COVID‐19, può avere un impatto sulle strategie di sostentamento e di conservazione che si basano sulle interazioni tra uomo e gli animali selvatici, come il turismo e la ricerca volti all'osservazione e allo studio della fauna selvatica. Ciò è particolarmente rilevante per la conservazione delle scimmie antropomorfe, dal momento che gli uomini e le scimmie antropomorfe possono essere infettati dagli stessi o simili patogeni. Sono richieste strategie basate su evidenze scientifiche che possano aiutare a prevenire la trasmissione di malattie infettive tra le antropomorfe e le persone che sono coinvolte nel turismo o vivono in prossimità di siti turistici. Lo sviluppo di linee guida per diminuire il rischio della trasmissione di malattie infettive e la loro effettiva applicazione richiede una comprensione dei fattori che influenzano il rispetto di tali linee guida da parte dei visitatori. Abbiamo somministrato un questionario a un campione di visitatori internazionali passati ( N  = 420) e futuri ( N  = 569) di siti turistici delle scimmie antropomorfe in Africa per descrivere i loro comportamenti, valutare le loro aspettative (ad esempio riguardo la consentita prossimità nei confronti degli animali) e identificare i fattori chiavi associati al potenziale rispetto delle misure di mitigazione della trasmissione di malattie uomo‐animale. Ciò è stato conseguito adottando un modello preso in prestito dalla letteratura medica (l'Health Belief Model; HBM), che si focalizza particolarmente nel ridurre la trasmissione del COVID‐19 in una fase iniziale della pandemia. I visitatori hanno espresso un minor desiderio di essere vaccinati contro il COVID‐19 (la cui somministrazione, nel periodo in cui il questionario è stato condotto, era appena iniziata nei confronti dei soggetti ad alto rischio), di indossare la mascherina durante il trekking (sebbene fossero disposti ad indossarla in presenza delle scimmie antropomorfe) e di fare una quarantena dopo un volo internazionale prima di vedere le scimmie. La nazionalità, le aspettative riguardo l'esperienza da visitatore e l'efficacia percepita di specifiche misure sono risultati dei fattori importanti nello spiegare la variazione nel rispetto delle linee guida da parte dei visitatori. Attraverso una migliore comprensione dei fattori che influenzano il rispetto delle misure di mitigazione della trasmissione delle malattie uomo‐animale, abbiamo ottenuto dati utili che sono essenziali per valutare la fattibilità, facilitare l'efficace comunicazione, e guidare l'attuazione di tali misure presso i siti turistici delle scimmie antropomorfe, con notevole importanza, non solo per prevenire la trasmissione del COVID‐19, ma anche la trasmissione di altre malattie infettive, specialmente in una fase iniziale di una futura pandemia. Mentre tali dati richiedono una gestione adattativa della situazione, in relazione alla sua evoluzione (ad esempio se la vaccinazione diventa accessibile a un gruppo più ampio di persone), essi contribuiranno a un'esperienza da visitatore più sostenibile che può effettivamente produrre risultati positivi sia per le persone che la biodiversità. Kikemikali: Kuibuka kwa magonjwa ya kuambukiza, kama vile Covid‐19, inaathiri mikakati ya maisha na zana za hifadhi zinazotegemea ushirikiano wa wanyamapori, kama vile utalii wa utafiti wa wanyamapori na utafiti. Hii ni muhimu hasa kwa uhifadhi mkubwa wa ape, kama wanadamu na apes kubwa huathiriwa na vimelea sawa. Mikakati ya msingi ya ushahidi inahitajika kuzuia maambukizi ya ugonjwa wa kuambukiza kwa apes kubwa na watu wanaohusika, au wanaoishi karibu na maeneo ya utalii. Maendeleo ya mapendekezo ya magonjwa na ufanisi waoutekelezajiInahitaji uelewa wa kile kinachoathiri kufuata mgeni. Kulingana na sampuli ya kimataifa ya zamani ( N  = 420) na wageni wa baadaye ( N  = 569) kwa maeneo makubwa ya utalii wa Afrika katika Afrika, tulitumia donsorey onlinetabiaMazoezi ya wageni, tathmini matarajio (k.m., kuhusu ukaribu na apes kubwa) na kutambua mambo muhimu kuhusiana na uwezo wa kufuata hatua za kupunguza magonjwa. Hii ilitekelezwa kurekebisha mfumo kutoka kwa maandiko ya afya (mfano wa imani ya afya; HBM), Hasa kulenga kupunguza maambukizi ya Covid‐19 katika hatua ya mwanzo ya janga hilo. Wageni walionyesha nia ya kuwa na chanjo dhidi ya Covid‐19 (ambayo, wakati uchunguzi wetu ulifanyika, ulikuwa umeanza tu kutumiwa kwa makundi ya hatari sana), amevaa facemask wakati wa safari (ingawa tayari wakati wa kutazama apes) na karantini baada ya kusafiri kimataifa kabla ya kutembelea apes kubwa. Mkoa wa utaifa, matarajio kuhusu uzoefu wa mgeni na ufanisi wa ufanisi wa hatua maalum walikuwa mambo muhimu kuelezea tofauti katika kufuata uwezotabia. Kwa kupata ufahamu bora wa kile kinachofanya ufuatiliaji na hatua za kupunguza magonjwa, tulipata ufahamu ambao ni muhimu kwa kutathmini uwezekano, kuwezesha mawasiliano bora, na utekelezaji wa utekelezaji katika maeneo makubwa ya utalii wa uzazi na umuhimu tu kwa wakazi wa miaka 19 lakini pia magonjwa mengine ya kuambukiza zaidi, hasa katika hatua za mwanzo za kondomu za baadaye. Wakati unahitaji kuhitaji usimamizi wa kutosha kama hali ya evolve (k.m. chanjo kuwa inapatikana zaidi), haya yatasaidia uzoefu zaidi wa wageni wa kudumu ambao unaweza kutoa matokeo mazuri kwa watu na viumbe hai. 摘要: COVID‐19等一些人兽共患的传染性疾病的出现，影响了以人和野生动物相互作用为基础的动物生存策略以及相关保护措施的实施，例如野生动物生态旅游、对野生动物的相关研究等。而由于人类和类人猿更易受相同病原体的感染，科学合理地应对人兽共患病，在类人猿相关的生态旅游及保护中就显得尤为重要。 因此，研究者有必要通过循证来采取有效手段，以防止人兽共患的传染性疾病在类人猿、游客以及旅游景点附近居民中的传播。而相关疾病安全建议的制定及其有效实施，则需要研究者对影响游客对这些措施遵从性的相关因素进行深入的调查和了解。 我们通过对曾经到过非洲野生类人猿旅游景点的420位游客以及569位有此意向的潜在游客进行了线上问卷调查，了解了游客在旅游中对人兽互动的预期(比如是否打算接近类人猿个体)、具体做法，以及游客是否遵从疾病防御措施的相关影响因素。这是基于健康信念模式(Health Belief Model; HBM)为理论基础编制的调查量表，旨在疫情初期减少COVID‐19的传播。 调查显示，游客对接种新冠疫苗(该调查进行时，新冠疫苗刚开始在高风险人群中接种)、徒步旅行时佩戴口罩(尽管愿意在参观类人猿时佩戴口罩)的意愿较低，且不太愿意在国际旅行后、参观类人猿之前被隔离。游客的国籍区域、对旅行体验的预期以及对相关防御措施有效性的感知，是影响游客对规定行为遵从性的重要因素。 通过更好地了解影响人们对疾病防御措施遵从性的相关因素，我们对评估防御措施的可行性、促进有效沟通以及该措施在大型类人猿旅游景点的有效实施提供了重要见解，这不仅对COVID‐19，而且对其他传染性疾病的初期防御尤为重要。随着疫情的发展需要有适应性的管理措施(例如，新冠疫苗接种要更加普及)，这将有助于提供更加可持续的游客旅行体验，并为人类和生物多样性带来积极有效的成果。 Resumo: O aparecimento de doenças infeciosas, tais como a COVID‐19, tem impacto nas estratégias de subsistência e nos instrumentos de conservação dependentes das interações entre o homem e a vida selvagem, tais como o turismo de natureza e a investigação. Isto é particularmente relevante para a conservação de grandes símios, uma vez que os humanos e os grandes símios são suscetíveis de serem infetados por agentes patogénicos semelhantes. São necessárias estratégias baseadas em evidência para prevenir a transmissão de doenças infeciosas a grandes símios e a pessoas envolvidas em turismo ou que vivem perto de locais de turismo. O desenvolvimento de recomendações contra doenças e a sua operacionalização efetiva requer uma compreensão do que afeta o cumprimento por parte dos visitantes. Com base numa amostra internacional de visitantes anteriores ( N  = 420) e possíveis visitantes ( N  = 569) a sítios de turismo de grandes símios selvagens em África, utilizámos um questionário online para caracterizar as práticas dos visitantes, avaliar as expectativas (por exemplo, sobre a proximidade aos grandes símios) e identificar factores‐chave relacionados com o possível cumprimento de medidas de mitigação de doenças. Isto foi implementado adaptando um modelo da literatura sobre saúde (o "Modelo de Crença em Saúde"; HBM ), particularmente centrada na redução da transmissão COVID‐19 numa fase inicial da pandemia. Os visitantes expressaram estar menos dispostos a serem vacinados contra a COVID‐19 (que, na altura em que o nosso inquérito foi realizado, tinha apenas começado a ser administrada a grupos de muito alto risco), de usarem uma máscara facial durante as caminhadas (embora dispostos quando vissem os símios) e de ficarem de quarentena após a viagem internacional antes de visitarem os grandes símios. Região de nacionalidade, expectativas sobre a visita e a percepção da eficácia de medidas específicas foram fatores importantes que explicam a variação no possível cumprimento de vários comportamentos. Ao obter uma melhor compreensão do que promove o cumprimento das medidas de mitigação de doenças, obtivemos informação essencial para avaliar a viabilidade, facilitar a comunicação eficaz, e orientar a implementação em locais de turismo de grandes símios com importância não só para a COVID‐19 mas também para outras doenças infeciosas, particularmente nas fases iniciais de futuras pandemias. Embora exigindo uma gestão adaptativa à medida que as situações evoluem (por exemplo, a vacinação torna‐se mais amplamente acessível), esta informação contribuirá para uma experiência mais sustentável do visitante que pode efetivamente produzir resultados positivos para as pessoas e a biodiversidade. Resumen: La aparición de enfermedades infecciosas, como la COVID‐19, afecta a las estrategias de subsistencia y a las herramientas de conservación que dependen de las interacciones entre los seres humanos y la vida silvestre, tales como el turismo basado en la fauna silvestre o la investigación. Esto es particularmente relevante para la conservación de los grandes simios, ya que los humanos y los grandes simios son susceptibles de ser infectados por patógenos similares. Para prevenir la transmisión de enfermedades infecciosas a los grandes simios, así como a las personas involucradas en sitios turísticos o que viven cerca de ellos, son necesarias estrategias basadas en evidencias científicas. El desarrollo y efectividad operacional de recomendaciones de protección frente a enfermedades, requiere comprender los factores que afectan su cumplimiento por parte de los visitantes. Basándonos en una muestra de visitantes internacionales que acudieron el pasado a sitios de grandes simios en África ( N  = 420), así como potenciales visitantes que planean visitarlos en un futuro ( N  = 569) utilizamos un cuestionario online para caracterizar sus prácticas, evaluar sus expectativas (p. ej., sobre la proximidad a los grandes simios) e identificar los factores clave relacionados con el cumplimiento de medidas de mitigación de enfermedades. Esto fue implementado adaptando un marco metodológico procedente de la literatura de la salud (el Modelo de Creencias de Salud; HBM), enfocado especialmente a reducir la transmisión de la COVID‐19 en una etapa temprana de la pandemia. Los visitantes expresaron menos disposición a vacunarse contra el COVID‐19 (en el momento en que se realizó nuestro cuestionario, comenzaba a administrarse solo a los grupos de alto riesgo), usar una mascarilla durante el trekking (aunque si estaban dispuestos a usarla en caso de ir a ver a los grandes simios) y hacer cuarentena tras viajes internacionales antes de visitar a los grandes simios. La región de nacionalidad, las expectativas sobre la visita y la eficacia percibida de la medida en cuestión, fueron factores importantes que explican la variación en el cumplimiento potencial de varios comportamientos. Al obtener una mejor comprensión de aquello que fomenta el cumplimiento de las medidas de mitigación de enfermedades, obtuvimos conocimientos que son esenciales para evaluar su viabilidad, facilitar su comunicación efectiva, y guiar su implementación en los sitios turísticos de grandes simios. Esto no solo es aplicable para la COVID‐19, sino también para otras enfermedades infecciosas a gran escala, particularmente en las primeras etapas de futuras pandemias. Si bien será necesaria una gestión adaptativa a medida que evolucionen las situaciones (por ejemplo, que la vacunación sea más accesible), esto puede contribuir a una experiencia de visitante más sostenible que genere resultados positivos para las personas y la biodiversidad. सार: कोभिड १९ जस्ता संत्रफमक रोगका उत्पतिल मानव वन्यजन्त अर्न्तत्रिफ्यामा आश्रित जिविकोपार्जन र संरक्षणका गतिविधि जस्त वन्यजन्तु आश्रित पर्यटन र अनुसन्धानलाइ नकारात्मक प्रभाव पारेका छ । या समस्या मुख्यत वानर संरक्षणमा लाग भएका पाइन्छ, किनकी मानव र वानर उस्त प्रकारका रोगजनक किटाण बाट ग्रस्त हुन सम्भावना बढि हुन्छ । पर्यटकीय क्षेत्रमा वा त्यस नजिक बसोबास गन मानव समुदायमा वानरबाट मानवमा वा मानवबाट वानरमा संत्रफमक रोग सन नदिन तथ्यमा आधारित रणनीतिका आवश्यकता छ । रोगबाट सुरक्षित रहन रणनीतिका विकास र त्यसका प्रभावकारी कार्यान्वयनका लागि पर्यटकल लिनुपन सावधानीका उचित बुभफइ हुन अत्यन्त जरुरी छ । पछिल्ला वषमा अप्रिफ्की वानर पर्यटन क्षेत्रमा आएका अर्न्तराष्ट्रिय पर्यटक (४२०) र भविष्यका संभावित पर्यटक (५६९) लाइ हामील अनलाईन प्रश्नावलीबाट उनीहरुका अभ्यासहरु, आकांक्षाहरु (उदाहरणका लागी वानरसग कति नजिक हुन चाहन) र संत्रफमक रोग न्यूनीकरण गर्नका लागि अपनाउन सम्भावित उपायहरुका पालना कतिका गन चहान्छन भनी सोधेका थिया । या प्रश्नावली हामील स्वास्थ्य क्षेत्रमा विद्यमान अध्ययनहरु, मुख्यत कोभिड १९ महामारी का प्रारम्भिक चरणमा संत्रफ्मणका जोखिम न्यूनीकरण गन अध्ययनका आधारमा तयार पारी लाग गरेका थिया । हाम्रा अध्ययनल पर्यटकहरुल कोभिड १९ का विरुद्घ खोप लगाउन ईच्छा नदेखाएका (अध्ययन अवधिमा भर्खर अति संवेदनशील समुहका लागि खोप अभियान सुरु भएका थियो), ट्रेकिङ्गका समयमा मास्क लगाउन अनिच्छा देखाएका (वानर हेन समयमा भने लगाउन सहमत), र अर्न्तराष्ट्रिय यात्रा पछि र वानर हेन अगाव केहि समय क्वारेन्टाइनमा बस्न अनिच्छा देखाएका देखिया । उल्लेखित नतिजाहरु राष्ट्रियता, पर्यटकीय अनुभव र संत्रफमक रोग न्यूनीकरण गर्नका लागि अपनाउन सम्भावित उपायहरुका प्रभावकारिताहरु जस्ता महत्वपूण कारणका आधारमा आएका पनि हामील पाया । संत्रफमक रोग न्यूनीकरण गर्नका लागि अपनाउन सम्भावित उपायहरु पालना गराउनका निम्ति आवश्यक कुराहरु केक हुन भन्न कारणका उचित बुभफइका आधारमा हामील केही महत्वपूण बुदाँहरुका, जस्त सम्भाव्यता मूल्यांकन, प्रभावकारी संवाद, र वानर पर्यटकीय क्षेत्रमा रोग न्यूनीकरणका उपायहरु (कोभिड १९ मात्र नभएर अरु संत्रफमक रोगहरु न्यूनीकरणका निम्ति पनि, मुख्यत भविष्यमा आउन सक्न अरु महामारीलाइ प्रारम्भिक चरणमै प्रभावकारी ढङ्गल लडनका निम्ति) अन्तर्दृष्टि पाएका छा । बदलिदा परिस्थिती अनुरुप व्यवस्थापन गदा (उदाहरणका लागि, प्रभावकारी खोप पहुँच) दिगा पर्यटकीय अनुभव दिन सकिन्छ, जसल मानिस र जैविक विविधता दुव प्रति सकारात्मक नतिजा दिन सक्छ ।